Static and mobile data gathering techniques in Wireless Sensor Networks: a survey - M. Ghaleb, Mukhtar; Subramaniam, Shamala; Othman, Mohamed; Ahmad Zulkarnain, Zuriati (Advanced Institute of Convergence Information Technology, 2014)
Wireless Sensor Networks (WSNs) have continued tremendous by towards the change of human civilization from different perspectives which emerged as an effective solution for many applications. WSN consists of hundreds of tiny sensors which deployed in specific area for a specific purpose, while the data is the precious value stand behind the needs for WSN that play a significant role in human life. Communication between nodes in the deployment area is a must to send data from all sensors to reach the base station and then to the end user. One fundamental factor that affects energy dissipation for each sensor is determined based on the communication techniques used to collect and deliver the data which has a direct impact on the lifetime of the whole network. In this paper, we present a taxonomy of data gathering algorithms in WSNs for the static-based and mobile-based architectures. In addition, we present an overview of each technique, and highlighted the features and drawbacks of each one. An extensive survey was provided including the variety of existed data gathering technique.